Choroideremia – A clinical insight and differential diagnosis (Ukrainian Journal of Ophthalmology, 2025)
Choroideremia is an X-linked recessive inherited, bilateral progressive chorioretinal dystrophy/degeneration leading to blindness by late adulthood. However, it can be confused occasionally with other conditions, especially retinitis pigmentosa due to their shared clinical manifestations. Since the management and patients' counseling differ between those conditions listed in the differential diagnosis, it is important for clinicians to come to the right diagnosis. This article is trying to make a differential diagnosis between choroideremia and other conditions based on the current knowledge of these disorders.
Keywords: Retinal dystrophy; Choroideremia; Retinitis pigmentosa; Chorioretinal degeneration; Differential diagnosis